Nevus lipomatous cutaneous superficialis: case report and review of the literature. - Xará, J.; Flor, D.; Relvas, M.; Cardoso, J.; Ramos, L. (European Journal of Pediatric Dermatology, 2024)
Nevus lipomatosus cutaneous superficialis (NLCS) is a rare benign cutaneous hamartoma that is poorly recognized and often misdiagnosed as a lipofibroma, cutaneous fibroma, infantile hemangioma, lymphangioma, or focal dermal hypoplasia. Histopathology is essential for diagnosis. We present the case of a 12-year-old girl with multiple asymptomatic lesions on the right buttock, which progressively enlarged. Early correct diagnosis and adequate therapeutic interventions are essential to minimize the esthetic impact of NLCS.